2016
DOI: 10.1186/s40792-016-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Resection of an esophageal schwannoma with thoracoscopic surgery: a case report

Abstract: BackgroundEsophageal schwannomas are rare primary submucosal esophageal tumors. We herein report a case of an esophageal schwannoma that was difficult to diagnose.Case presentationA 39-year-old woman presented with chief complaints of difficulty swallowing and epigastric pain. Enhanced computed tomography of her chest revealed a tumor mass at the upper thoracic esophagus with internal heterogeneity. 18-Fluorodeoxyglucose positron emission tomography/computed tomography showed a hypermetabolic appearance matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
(18 reference statements)
0
16
0
1
Order By: Relevance
“…A giant esophageal submucosal tumor has been reported, which required esophagectomy [4]. Thoracoscopic excision of esophageal submucosal tumor was feasible [5]. In our presenting case of esophageal submucosal tumor, thoracoscopic enucleation was very useful because the 3.6 cm tumor was easily identified and excised without difficulty.…”
Section: Commentsmentioning
confidence: 83%
“…A giant esophageal submucosal tumor has been reported, which required esophagectomy [4]. Thoracoscopic excision of esophageal submucosal tumor was feasible [5]. In our presenting case of esophageal submucosal tumor, thoracoscopic enucleation was very useful because the 3.6 cm tumor was easily identified and excised without difficulty.…”
Section: Commentsmentioning
confidence: 83%
“…Sato et al reported that cases with tumor size of 50 mm or more, and tumor location at the upper esophagus, usually required thoracotomy[ 1 ]. Watanabe et al[ 6 ] reported the need to convert from thoracoscopic enucleation to thoracoscopic subtotal esophagectomy owing to the location of an esophageal schwannoma at the upper thoracic esophagus, and its size being in excess of 50 mm. Therefore, thoracotomy or esophagectomy would be usually chosen for tumors that are 50 mm or more in size or located in the upper and middle thirds of the thoracic esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…The left thoracic approach, although considered better for tumors involving the left esophageal wall, is limited by the presence of the aortic arch and the trachea. In addition, the choice between thoracoscopy or thoracotomy is made depending on the size and/or location of the tumor[ 1 , 5 , 6 ]. Submucosal endoscopic tumor resection (SET) for esophageal SMT, was recently reported by Inoue et al[ 7 ], using the technique of submucosal tunnel described for per-oral endoscopic myotomy (POEM) for esophageal achalasia[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…High FDG uptake is generally found in malignant tumors. While esophageal schwannomas are benign tumors, it shows a hypermetabolic appearance on FDG-PET [ 10 , 11 ]. Furthermore, endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) can be used to help establish the pathologic diagnosis, but this technique has limited accuracy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment for benign esophageal tumors arising from the submucosal layer is controversial. In general, surgical resection should be considered for patients with benign esophageal tumors which are large, symptomatic, or increasing in size [ 11 ]. Additionally, suspected malignant potential is usually considered to be an indication of an extended operation such as total esophagectomy.…”
Section: Introductionmentioning
confidence: 99%